Effect of 0.01% Atropine on Accommodation in Myopic Teenagers - Li, Huixia; Zhang, Liying; Tian, Hong; Zhang, Song; Zhang, Xueyan; Zhang, Han; Chen, Yujing; Qi, Wenping; Wu, Xiaoying; Jiang, Hongmei; Yang, Hailong; Yang, Yajun; et al. (Frontiers in Pharmacology, 2022)
Purpose: In order to evaluate the effects of 0.01% atropine eye drops on accommodative system parameters among teenagers with low-myopia. Methods: 95 myopic teenagers (39 boys (8.69±2.473) and 56 girls (8.54±2.054) aged 5–17 years) with no history of eye disease were enrolled. Biometric and accommodative system parameters were evaluated before and 1 week, 1 month, 3 months as well as 6 months 0.01% atropine eye drops instillation. Results: Participants without accommodative demand at 6 months demonstrated insignificant changes after the atropine instillation (all P > 0.05). However, there were significant differences in accommodative sensitivity, accommodative amplitude, accommodative responsiveness and negative relative accommodation (NRA) at 3 months compared with baseline after atropine instillation (all P < 0.05). Except spherical equivalent refraction, cornea thickness, intraocular pressure, and axial length were stable after the 0.01% atropine instillation (all P > 0.05). Conclusions: Morphologically, current measurements suggested 0.01% atropine had favorable reduction of accommodation for childhood low myopia over a half-year period.